PENGARUH DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA INDUSTRI SAMBEL PECEL WAHYU TUMURUN MADIUN. - Ninik Srijani (Universitas PGRI Madiun, 2014)
This study aims to examine the effect of labor discipline on employee performance . Discipline is one of the factors that affect the performance of employees . Good work discipline of an employee will affect the performance of employees , so the work will be completed effectively and efficiently . The samples in this study using a sample that is saturated all employees sauce Industry pecel WAHYU TUMURUN Madiun as many as 20 people were sampled in this study. Data collection method using a questionnaire with Likert scale to explore the data and performance of employees working Discipline sauce Industry pecel WAHYU TUMURUN Madiun.Based on the results obtained by the magnitude of the F test results obtained by the value of F is 10.756 4.414 was Ftable Sighitung0 magnitude on the other hand , 004 and Sigprob 0.05 this means that the value of F ≥ F table ( 10.756 ≥ 4.414 ) or ≤ Sighitung Sigprob ( 0.004 ≤ 0 , 05 ). In the t-test can be made following the regression line Y = 8.442 + 0.741 X, meaning that if the increased labor discipline one employee 's performance will increase as much as 0,741 % , if other factors remain . The value of t is 3.280 and 1.734 T Table , on the other hand the magnitude Sighitung Sigprob 0.004 and 0.05, this means that the value of t ≥ t table ( 3.280 ≥ 1.734 ) or ≤ Sighitung Sigprob ( 0.004 ≤ 0.05 ) . On the basis of correlation test , F test and t-test it can be concluded that there is influence between the Employee Performance Discipline Work on pecel sauce company WAHYU TUMURUN Madiun.